“Dea Corona”: The Image of Nang Songkran’s Body and the Perspective of Thai People under the COVID-19 Pandemic - Werojruedee, Virat (Journal of Letters, 2022)
The aim of this research article is to analyze the image of Dea Corona and to criticise the government’s management under the COVID-19 Pandemic, as well as to describe the manner that implies that Thai people refer to China as the origin of the coronavirus. The content analysis was used to compare 10 images from the Facebook and the framework of the rhetoric methods hidden in the images of Dea Corona and comments under them in the contemporary Thai social context. The results show that the image of Dea Corona has both positive and negative aspects in one body. Both the image and the rhetoric methods that appear in the comments under her pictures reflect the views that some Thai people have on the situation of the Covid-19 epidemic in 3 ways: 1) "Dea Corona" as Village Health Volunteer 2) "Dea Corona" with criticism of the failure to manage the covid 19 epidemic 3) Thai people look at China with inveighing through "Dea Corona"